29.1k views
3 votes
Find the inverse function of g(x) = 2x + 4. g -1(x) = 4x + 2 g -1(x) = 2x + g -1(x) = x - 2 g -1(x) = 2x - 4

2 Answers

6 votes

Answer:


f^(-1)=(x)/(2) -2

Explanation:

the inverse function of g(x) = 2x + 4

To find the inverse of a function we replace g(x) with y


y=2x+4

Replace x with y and y with x


x=2y+4

Solve the equation for y

Subtract 4 from both sides


x-4= 2y

Divide both sides by 2


(x)/(2) -2=y


y=(x)/(2) -2

Replace y with f inverse


f^(-1)=(x)/(2) -2

User Rahul Paru
by
5.4k points
4 votes

For this case we must find the inverse of the following function:


g (x) = 2x + 4

Replace g(x) with y:


y = 2x + 4

We exchange the variables:


x = 2y + 4

We solve for "y":

We subtract 4 on both sides of the equation:


x-4 = 2y

We divide between 2 on both sides of the equation:


y = \frac {x} {2} -2

We change y by
g ^ {-1} (x):


g ^ {- 1} (x) = \frac {x} {2} -2

Answer:


g ^ {- 1} (x) = \frac {x} {2} -2

User Mark Korzhov
by
5.7k points